Key Point to Creation? - Spaargaren, Maarten (Homœopathic Links, 2013)
Is there, from a homeopathic viewpoint, a universal key from which Creation has been built up? Is there a building plan that gives clarity to the workings of Creation and its inherent developments? In this article the story of the investigation of these questions is described in the setting of a 30-year-old homeopathic practice for chronically sick people. We will successively discuss the discovery of the key, the key itself and the perspectives of the key. A special link to the current developments of mankind is made.
Keywords: LEAM; Layered electro acupuncture measurement; Energy body; Energy patterns; Constitutional types; Development